Is the insulin necessary for the struggle against oxidative stress in diabetes mellitus type 2 – a pilot study - Salatić, Igor; Dragović, Tamara; Stevanović, Ivana; Drašković Pavlović, Biljana; Ninković, Milica (Vojnosanitetski pregled, 2022)
Background/Aim. Hyperglycaemia has a detrimental effect on the progress of micro/macrovascular complications in patients with diabetes mellitus type 2 (T2DM). Additionally, all known complications in T2DM are coupled with oxidative stress developed from different metabolic pathways. The aim of this study was to estimate the quality of glucoregulation and the degree of oxidative stress in T2DM patients depending on the applied therapeutic protocol and assess their correlation with clinical data and crucial biochemical parameters important for the development of diabetes complications. Methods. All included patients were divided into two groups: those treated with oral antidiabetic drugs (OAD) and those treated with oral antidiabetic drugs and insulin (OADINS). Thiobarbituric acid reactive substances (TBARS), total sulfhydryl groups (TSH), the activity of superoxide dismutase (SOD), total nitrites (NOx), vascular endothelial growth factor (VEGF), and activities of matrix metalloproteinase 9 (MMP9) were measured, together with lipid profile and routine biochemical parameters. All subjects were analyzed for demographic characteristics and detailed medical history as well as smoking habits and calculated for body mass index (BMI). Results. All patients were uniformly poor glucoregulated and dyslipidemic. SOD activity was decreased, and lipid peroxidation was increased in the OAD group compared to OADINS. Deficient glucoregulation in both the OAD and the OADINS groups did not associate with an oxidative state outcome. In both of these groups, the concentrations of VEGF and MMP9 were significantly higher than in controls. Conclusion. The better antioxidative outcome, expressed with a normalized concentration of TBARS, preserved TSH, and normalized SOD activity in T2DM patients treated with OADINS compared to those treated exclusively with OAD, suggests the need for more careful consideration of earlier insulin introduction into T2DM therapy in order to prevent the development of complications.